2016
DOI: 10.1186/s12864-016-2462-3
|View full text |Cite
|
Sign up to set email alerts
|

ACTN3 R577X and ACE I/D gene variants influence performance in elite sprinters: a multi-cohort study

Abstract: BackgroundTo date, studies investigating the association between ACTN3 R577X and ACE I/D gene variants and elite sprint/power performance have been limited by small cohorts from mixed sport disciplines, without quantitative measures of performance. Aim: To examine the association between these variants and sprint time in elite athletes.MethodsWe collected a total of 555 best personal 100-, 200-, and 400-m times of 346 elite sprinters in a large cohort of elite Caucasian or African origin sprinters from 10 diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
88
0
21

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(111 citation statements)
references
References 37 publications
2
88
0
21
Order By: Relevance
“…Subsequently, replication in national/international level athlete cohorts from Finland (Niemi & Majamaa, ), Greece (Papadimitriou, Papadopoulos, Kouvatsi, & Triantaphyllidis, ), Russia (Druzhevskaya, Ahmetov, Astratenkova, & Rogozkin, ), Israel (Eynon et al., ), and Poland (Cieszczyk et al., ) have been reported. A subsequent analysis of sprint/power cohorts also found that the ACTN3 RR genotype has a stronger association with sprinters compared with other track and field events such as jumpers, pole‐vaulters, decathletes, and throwers (Papadimitriou et al., ; Papadimitriou et al., ) and no Olympic‐finalist sprinter has yet been identified with the 577XX genotype (Eynon et al., ). Similarly, four Asian sprint/power cohorts from Taiwan (Chiu et al., ), Japan (Kikuchi et al., ; Mikami et al., ), Korea (Hong & Jin, ; Kim, Song, & Kim, ), and China (Yang et al., ) have also confirmed the lower ACTN3 XX frequency in elite sprinters compared with population controls (Table a).…”
Section: Actn3 R577x and Human Muscle Performance: The ‘Speed Gene’mentioning
confidence: 98%
“…Subsequently, replication in national/international level athlete cohorts from Finland (Niemi & Majamaa, ), Greece (Papadimitriou, Papadopoulos, Kouvatsi, & Triantaphyllidis, ), Russia (Druzhevskaya, Ahmetov, Astratenkova, & Rogozkin, ), Israel (Eynon et al., ), and Poland (Cieszczyk et al., ) have been reported. A subsequent analysis of sprint/power cohorts also found that the ACTN3 RR genotype has a stronger association with sprinters compared with other track and field events such as jumpers, pole‐vaulters, decathletes, and throwers (Papadimitriou et al., ; Papadimitriou et al., ) and no Olympic‐finalist sprinter has yet been identified with the 577XX genotype (Eynon et al., ). Similarly, four Asian sprint/power cohorts from Taiwan (Chiu et al., ), Japan (Kikuchi et al., ; Mikami et al., ), Korea (Hong & Jin, ; Kim, Song, & Kim, ), and China (Yang et al., ) have also confirmed the lower ACTN3 XX frequency in elite sprinters compared with population controls (Table a).…”
Section: Actn3 R577x and Human Muscle Performance: The ‘Speed Gene’mentioning
confidence: 98%
“…This is likely to be the case for RYR1 mutations, in addition to what has been reported regarding variants/polymorphisms in the ACE and α-actinin-3 (ACTN3) genes. [54][55][56] In other rare situations, a combination of two genetic disorders may alleviate exercise-related phenotypes such as the coexistence of α-thalassaemia and sickle cell trait, lowering risk for exercise collapse associated with the sickle cell trait (ECAST). 57 Emerging evidence suggests that specific polymorphic variants in a number of genes also increase the susceptibility of developing ERM (table 2).…”
Section: Myoglobinuria and Arfmentioning
confidence: 99%
“…These are limitations of this study. In addition, there are already other factors that have been reported to show associations with sprinting ability, such as body mass, body mass index and height 32,33 , muscle fiber composition 34,35 and several genetic variants [36][37][38][39][40][41] .…”
Section: Discussionmentioning
confidence: 99%